Editorial: FDI in Central Europe - Krzysztof Wach (Entrepreneurial Business and Economics Review, 2014)
Literature offers numerous concepts, models, and theories explaining foreign direct investment (FDI) inflows and outflows. The most popular classification of these theories divides them into three groups (Kilic et al., 2014): macro-level theories, micro-level theories, and development theories, which combine elements of both macro- and microlevel theories (Wach & Wojciechowski, 2014; Wojciechowski, 2013).